Infectious Granuloma at the Peritoneal Dialysis Catheter Exit Site: A Case Report of MRSA-Associated Complication in a Young CAPD Patient - Rifai, Achmad; Manugan, Reizal Audi (Universitas Brawijaya, 2026)
Introduction: Exit-site infection (ESI) is one of the most frequent complications in CAPD patients and can progress to peritonitis if inadequately managed. Granulomatous ESI caused by MRSA remains sparsely reported in the literature. Case Presentation: A 20-year-old woman with end-stage kidney disease secondary to lupus nephritis, on CAPD for two years, presented with a five-day history of a moist, erythematous nodule (±1 cm) at the Tenckhoff catheter exit site with purulent discharge. The modified Schaefer exit-site score was ≥7, confirming active infection. There was no peritoneal involvement. Management and Outcome: Gram staining revealed Gram-positive cocci (3+), and culture confirmed MRSA susceptible to levofloxacin and TMP-SMX. Empirical oral ciprofloxacin 500 mg twice daily and topical gentamicin were initiated. Clinical improvement was observed at day seven. Therapy was then transitioned to oral TMP-SMX (cotrimoxazole 480 mg once daily) for an additional seven days. MRSA carrier screening via nasal and throat swabs was planned. Discussion: Empirical ciprofloxacin deviated from ISPD guidelines recommending anti-staphylococcal penicillin or first-generation cephalosporin. Transition to TMP-SMX post-culture was appropriate and guideline-concordant. The favorable outcome highlights the importance of microbiological confirmation and targeted therapy. Conclusion: MRSA-associated infectious granuloma at the CAPD exit site can present in young patients without systemic features. Timely microbiological workup, guideline-directed antibiotic therapy, and MRSA decolonization are essential to prevent progression to peritonitis.